2022
DOI: 10.3389/fpls.2022.870207
|View full text |Cite
|
Sign up to set email alerts
|

The Pomegranate Deciduous Trait Is Genetically Controlled by a PgPolyQ-MADS Gene

Abstract: The pomegranate (Punica granatum L.) is a deciduous fruit tree that grows worldwide. However, there are variants, which stay green in mild winter conditions and are determined evergreen. The evergreen trait is of commercial and scientific importance as it extends the period of fruit production and provides opportunity to identify genetic functions that are involved in sensing environmental cues. Several different evergreen pomegranate accessions from different genetic sources grow in the Israeli pomegranate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The expression of the FLC -like gene of this species correlates with the inhibition of flowering in plants with developing fruits [ 76 ]. For Punica granatum belonging to the order Myrtales that diverged from Brassicales about 110 MYA), it has been found that deleterious mutations of an FLC -like gene result in evergreen rather than deciduous trees [ 77 ]. In Malus domestica , belonging to Rosales, of which the most recent common ancestor (MRCA) with Brassicales existed about 120 MYA, expression of FLC -like genes s.l.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the FLC -like gene of this species correlates with the inhibition of flowering in plants with developing fruits [ 76 ]. For Punica granatum belonging to the order Myrtales that diverged from Brassicales about 110 MYA), it has been found that deleterious mutations of an FLC -like gene result in evergreen rather than deciduous trees [ 77 ]. In Malus domestica , belonging to Rosales, of which the most recent common ancestor (MRCA) with Brassicales existed about 120 MYA, expression of FLC -like genes s.l.…”
Section: Discussionmentioning
confidence: 99%